Histone lysine dimethyl-demethylase KDM3A controls pathological cardiac hypertrophy and fibrosis - Qing-Jun Zhang (Nature Portfolio, 2018)
Histone lysine demethylases (KDMs) can mediate transcriptional reprogramming in disease states. Here the authors show that KDM3A promotes left ventricular hypertrophy and cardiac fibrosis by activating the transcription of Timp1, and that pharmacological inhibition of KDM3A attenuates cardiac remodeling induced by pressure overload.